ANALYSIS OF HUMAN RESOURCES COMPETENCY DEVELOPMENT STRATEGY AMONG GEN Z IN FACING THE ERA OF SOCIETY 5.0 THROUGH THE SOAR METHOD CASE STUDY: PT. X - Ruth Meylina Manik; Yeni Absah; Anizar (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
The research used in the thesis entitled "Analysis of Human Resource Management Competency Development Strategy among Gen Z in Facing the Society 5.0 Era through the SOAR Method Case Study: PT. X (Persero) Tbk" is a descriptive and exploratory research. The research location was conducted at PT X (Persero), Tbk which is located in Menara Mandiri, Medan City, North Sumatra. The method used to analyze this strategy is the SOAR Method. The research population is all Gen Z employees who work at PT. X (Persero) Tbk Region I/Sumatera 1. Based on data obtained from the Human Capital (HC) department, the number of employees of PT. X Region I/Sumatera 1 who are included in the Gen Z category is 200 people. This population consists of various departments and positions within the company, both those working in regional offices, areas and branches. So the number of respondents who will be used as samples in this study is 133 employees. Based on the results of the data analysis, the following conclusions were obtained: PT's strategy. X (Persero) Tbk in managing HR development is carried out through a holistic, technology-driven approach, oriented towards employee welfare and continuous innovation. This is supported by various programs that have been designed to prepare employees to face digital and social challenges in the future. The main obstacle in developing the competency of Gen Z employees is the lack of time to attend training. Lack of time is the main obstacle because employees are often busy with routine tasks and tight work targets, making it difficult to take the time to attend training programs provided by the company. The strategy that has been implemented by PT. X (Persero) Tbk is good but not yet effective because Gen Z employees cannot attend training programs provided by PT. X (Persero) Tbk due to lack of time to attend training. Generation Z employees have high internal strengths (Strengths), especially in mastery of digital technology, critical thinking skills, and learning motivation. This is reflected in the average score of the Strengths dimension of 4.42. Organizational support in terms of development opportunities (Opportunities) is still classified as moderate with a score of 3.13. This shows the need for increased training, career guidance, and a culture of innovation to support Gen Z growth. Gen Z employees' aspirations for career development and contribution to the company are very high, with an average score on the Aspirations dimension reaching 4.78. This shows their readiness and enthusiasm to play an active role in organizational transformation. Gen Z employees show high confidence in the results of competency development (Results), with the highest score among all dimensions, namely 4.86. This reflects their optimism about the benefits of the training and learning carried out. The most effective competency strategy is Workshop/Seminar. This is evident from the high percentage of respondents who chose this strategy, namely 51.1%. This activity allows employees to acquire the latest knowledge and skills in a short time, as well as providing an opportunity to interact directly with experts or practitioners in a particular field. This is very important in facing the challenges of rapid technological developments in the Society 5.0 era. Workshops/Seminars also support the networking process between employees and professionals, which can improve collaboration and team problem solving, which are important components in the competency development strategy for Gen Z who are very exposed to technological developments. Another effective competency development strategy is Mentoring/Coaching. Direct guidance from superiors or experienced mentors can develop technical and non-technical skills in more depth. More intense interaction between mentors and mentees makes the learning process more personal and relevant to the challenges faced. This is very important in facing the Society 5.0 era, where rapid technological changes require employees who have adaptive and innovative skills. Mentoring/Coaching is an integral part of an effective competency development strategy, especially in preparing Gen Z to pursue a successful career in the world of work.